2019
DOI: 10.1155/2019/4051206
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET/CT Imaging in Advanced Glottic Cancer: A Tool for Clinical Decision in Comparison with Conventional Imaging

Abstract: This study assessed the role of 18F-FDG PET-CT (PET/CT) to detect the cartilage and paraglottic infiltration in advanced glottic cancer comparing the results with those of conventional imaging (CI) (contrast-enhanced computed tomography and/or magnetic resonance). In addition, we assessed the prognostic value of quantitative parameters, measured on baseline PET/CT, in terms of event-free survival (EFS) and overall survival (OS). We retrospectively analyzed 27 patients with glottic squamous cell carcinoma stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…disease-free survival (p =0.03), while nodal SUV was not predictive. Castelli et al (23) and Paone et al (24) concluded that among many quantitative PET parameters, SUVmax did not show promising results as a good outcome predictor. However, Chun et al (25) claimed that there was a significant difference in SUVmax between cervical lymph nodes with and without extracapsular spread (6.39 ± 4.53 vs 1.21 ± 1.70; p < .001) in patients with laryngeal cancer who had undergone 18F-FDG PET/CT before the surgery.…”
Section: Discussionmentioning
confidence: 98%
“…disease-free survival (p =0.03), while nodal SUV was not predictive. Castelli et al (23) and Paone et al (24) concluded that among many quantitative PET parameters, SUVmax did not show promising results as a good outcome predictor. However, Chun et al (25) claimed that there was a significant difference in SUVmax between cervical lymph nodes with and without extracapsular spread (6.39 ± 4.53 vs 1.21 ± 1.70; p < .001) in patients with laryngeal cancer who had undergone 18F-FDG PET/CT before the surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In the last decade, numerous studies have been performed to assess and compare the value of different imaging techniques in the evaluation of cartilage invasion [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, most of those studies have significant drawbacks, mainly small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging tests can also be used to evaluate cartilage invasion. Paone et al found that PET/CT improves the detection of cartilage invasion and overall staging [11]. Dual-energy CT has been shown to improve the accuracy of cartilage invasion imaging By contrast, dynamic contrast-enhanced CT does not appear to improve diagnostic accuracy in assessing cartilage invasion [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case demonstrated a primary NK/T-cell lymphoma involving the larynx revealed on PET/CT, which exhibited a diffuse FDG uptake on supraglottic and glottic exophytic regions 14 . Asymmetric vocal cord FDG uptake should arouse a suspicion of primary neoplasm, 15 metastasis, 16 vocal paralysis (contralateral side uptake), 17 myofibroblastic tumor, 18 myxoma, 19 and sarcoidosis 20 . In our case, the ENKTL involved the left side of vocal cord, showing focal intense FDG uptake on PET/CT.…”
mentioning
confidence: 99%